Combined neoadjuvant chemotherapy and immunotherapy in a hepatitis B virus-positive patient with locally advanced rectal adenocarcinoma: a case report and literature review - Li, Qiyun; Wu, Xue; Xu, Zhibin; Li, Taidong (Frontiers in Oncology, 2025)
Microsatellite-stable (MSS) rectal adenocarcinoma remains a therapeutic challenge, particularly in patients with complicating factors such as chronic hepatitis B virus (HBV) infection. Advances in immunotherapy, including immune checkpoint inhibitors (ICIs), have introduced new opportunities to improve the treatment outcomes in this subset, yet their application in HBV-positive cancer patients is less well understood. Here we report the case of a 46-year-old female with MSS locally advanced rectal adenocarcinoma and active HBV infection, successfully treated with cmFOLFOXIRI combined with camrelizumab as neoadjuvant therapy. The patient presented with a circumferential rectal mass, elevated tumor markers, and virological evidence of high HBV viral load, necessitating prophylactic antiviral management with entecavir. Following five cycles of cmFOLFOXIRI and two cycles of camrelizumab, significant tumor regression was achieved, with further response observed after long-course radiotherapy combined with irinotecan and capecitabine. Laparoscopic low anterior resection revealed complete pathological remission (pCR), with no residual tumor cells or lymph node metastases identified. This case underscores the potential of integrating immunotherapy into multimodal neoadjuvant regimens for MSS rectal cancer while highlighting the critical importance of HBV management to minimize reactivation risks during treatment. These findings offer valuable insights into the safe and effective use of ICIs in HBV-positive cancer patients, warranting further investigation in larger clinical studies.